Wildlife collections of Royal Palace Museums in The West Region of Cameroon with a focus on wildlife conservation - Mfonden Poumie, MM; Coals, P; Meutchieye, F; Fokam, OM (African Journals OnLine, 2021)
The royal palace museums of the Grassfields’ Kingdoms of West Region of Cameroon are well recognized for the preservation of culturally significant objects and practices. To date, the role of palace museums in wildlife conservation has received little consideration. Herein, a preliminary study into the animalbased artefacts of palace museums from a wildlife conservation perspective is presented. A total of 11 chiefdom palace museums in the West Region of Cameroon were surveyed and the animal species represented in their exhibitions recorded. Parts of 32 different animal species, including locally extinct large mammals such as lion, cheetah, chimpanzee, and elephant were found. The primary purpose for inclusion of specimens in palace museums was for preservation of culture. However, potential wildlife conservation focused uses to which palace museums may also put their collections are discussed herein.